STRUCTURE OPTIMISATION OF THREE PHASES OF TITANIUM DIOXIDE - Abdu, S. G.; Shu'aibu, A.; Nura, H. (FUDMA JOURNAL OF SCIENCES, 2023)
Titanium dioxide attracts great attention due to its many applications. It has been successfully employed in photocatalysis, paints, cosmetics, and medicine. It’s used in the development of a high efficiency dye sensitized solar cell. In this work, the Fritz-Haber Institut ab initio Molecular Simulation code, FHI-aims was used to investigate and obtain the most stable ground state atomic coordinates of the three major phases of TiO2.The exchange-correlation interactions are treated by the Linear Density Approximation. The ground state total energies were found to be; Rutile TiO2 -55653.8689758471 eV, Anatase TiO2 -109308.048965066eV and Brookite TiO2 -218614.36351209 eV.